The BER of the New FSO Receiver Manufactured by RTCVD and Solar Cell Technology - Qinggui Hu; Long Wenguang (International Journal of Optics)
In the free-space optical (FSO) communication system, alignment and coupling are key issues. In this work, we adopt a PIN photodiode board as the new receiver to address this question. Firstly, with rapid thermochemical vapor deposition (RTCVD) and solar cell technology, the PIN photodiode board is manufactured. Then, using scanning electron microscope (SEM) and transmission electron microscope (TEM), the microphotographs of the PIN photodiode are taken. After that, the PIN board is arranged as a new receiver in the FSO system to do a bit error rate (BER) experiment. In total, we have carried out 4 groups of experiments. The BERs of the ordinary receiver are as follows: (10−8.5, 10−8, 10−8, and 10−7.9) and that of the new receiver is (10−9.2, 10−9.1, 10−9.1, and 10−9), respectively. It means the BER of the new receiver is lower. In other words, the new receiver performs better.